Early efficacy of and toxicity from lutetium-177-DOTATATE treatment in patients with progressive metastatic NET. Issue 7 (July 2017) - Pencharz, Deborah; Walker, Martin; Yalchin, Mehmet; Quigley, Ann-Marie; Caplin, Martyn; Toumpanakis, Christos; Navalkissoor, Shaunak
Abstract : Objective: Lutetium-177 DOTA-D-Phe1-Tyr3-octreotide ( 177 Lu-DOTATATE) is a treatment option for patients with well-differentiated metastatic neuroendocrine tumours. Our centre started administering this therapy in 2012. The aim of this study was therefore to analyse the first cohort of patients treated with 177 Lu-DOTATATE to determine its early efficacy and toxicity. Patients and methods: We retrospectively analysed patient, tumour and treatment characteristics, end-of-treatment outcome, time to progression and toxicity in 79 consecutive patients treated with 177 Lu-DOTATATE who had progressive NET according to Response Evaluation Criteria in Solid Tumours criteria. Follow-up time was 12–40 months. Study of Kaplan–Meier plots, analysis of time to progression and multiple regression analysis of factors predictive of time to progression were performed. Results: At end-of-treatment radiological restaging, 13% of patients were found to have partial response and 64% to have stable disease; 23% of patients progressed through treatment. Overall, 47% of patients demonstrated a reduction in chromogranin A levels. The overall estimated median time to progression from the start of treatment was 28 months for the entire cohort and 31, 30 and 5 months for those with partial response, stable disease and progressive disease, respectively. On multivariate regression analysis, higher grade of tumour was found to be significantly associated with shorter progression-free survival. Three patients experienced grade 1 haematotoxicity, five grade 1 nephrotoxicity and one grade 2 nephrotoxicity. Conclusion: Early outcomes of patients treated with 177 Lu-DOTATATE are similar to those in previously published series in terms of end-of-treatment efficacy and toxicity. This provides further evidence that this is a safe and efficacious form of treatment for patients with progressive metastatic neuroendocrine tumours.